A produção das revistas científicas do Serviço Social sobre o envelhecimento e a Reforma da Previdência Social nos anos de 2019 e 2020 - Luz, Sônia Ferreira da (Universidade Federal do Tocantins, 2022)
This work entitled The production of social work scientific journals on aging and social security reform in the years 2019 and 2020, whose theme involves Aging and Social Security, addressing as a research object "Challenges for a person elderly with the social security reform in view of social benefits and retirement in the scientific production of Social Work", and as a general objective: To understand the scientific production of Social Work in what way the Social Security reform will reach an elderly person and as objectives Specifics: Identify the challenges faced by the elderly with the social security reform, given the changes in retirement by age and social benefits; Analyze the possible impacts of the Social Security Reform on the life of the elderly. As methodological, qualitative bibliographic research was used, which provided us with a better understanding of the analyzes under study, through the selection of articles published in 2019 and 2020, in the main Social Work magazines with themes that allowed us a better understanding of the object in study. The research was based on dialectical historical materialism as it allows us a better approach and understanding of reality. The results showed us that the Social Security counter-reform will cruelly affect the elderly Brazilian population that lives in precarious and informal jobs, consequently without access to retirement, and with obstacles and bureaucracies to access Social Benefit, something that is a citizen's right The elderly person still has to request legalization for access. However, there is a need to advance on this issue for a better understanding of the given reality, many changes, setbacks and loss of rights, considering that and Social Workers need to be aware of this scenario for a demystification and deepening of reality in the perspective of the realization of social rights.